Copper‐Based Metal‐Organic Framework Induces NO Generation for Synergistic Tumor Therapy and Antimetastasis Activity. Issue 4 (24th November 2022) - Ren, Debao; Cheng, Yibin; Xu, Wenxuan; Qin, Wenjun; Hao, Tonghui; Wang, Fei; Hu, Yun; Ma, Lixin; Zhang, Cheng
Abstract: The interaction between platelets and circulating tumor cells (CTCs) contributes to distal tumor metastasis by protecting CTCs from immunological assault and shear stress, which can be disrupted by nitric oxide (NO) through inhibiting platelet‐mediated adhesion. To eradicate primitive tumors and inhibit CTC‐based pulmonary metastasis, a novel biomimetic nanomedicine (mCuMNO) is designed by encapsulating Cu + ‐responsive S‐nitrosoglutathione as a NO donor into a copper‐based metal‐organic framework (CuM). This work discovers that mCuMNO can target tumor regions and deplete local glutathione (GSH) to reduce Cu 2+ to Cu +, followed by triggering NO release and hydroxyl radicals (· OH) production, thereby interrupting platelet/CTC interplay and contributing to chemodynamic therapy. Detailed studies demonstrate that mCuMNO exhibits high efficiency and safety in tumor therapy and antimetastasis activity, sheding new light on the development of CuM‐based tumor synthetic therapy. Abstract : A CuM with GSNO encapsulation is constructed to inhibit tumor growth and metastasis. High concentrations of glutathione (GSH) and H2 O2 in the tumor microenvironment reduce Cu 2+ to Cu +, which triggers nitric oxide (NO) release and · OH production, thereby interrupting platelet/CTC interplay and contributing to chemodynamic therapy (CDT).